The IJTMB as a Global Therapeutic Massage and Bodywork Resource - Porcino, Anthony (Multimed Inc., 2014)
The IJTMB has a broad international (non-North American) readership, representing about one-third of all visitors to the Journal. What are the facilitators and barriers relevant to use of and participation in the IJTMB for international therapeutic massage and bodywork (TMB) researchers, educators, and practitioners? How can the IJTMB continue its growth and international recognition? This editorial looks at some of the opportunities for increased international involvement and relevancy, and the advantage of being open access for the non-North American audience.